Soil Properties Affecting Mercury (Hg) Adsorption-Desorption: Determine The Extent of Soil Pollution Risk - Puji Hapsari Hurum; Suwardji; Taufik Fauzi; A. A. Ketut Sudharmawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
One of the hazardous wastes generated from unlicensed gold mining is mercury. Mercury is a toxic metal that can have a negative impact on the environment such as reducing soil and water quality and disturbing human health. The presence of mercury in the soil is completely controlled by adsorption-desorption of various sorbents. Soil properties greatly affect the adsorption and desorption of mercury in the soil. Because different soil properties will adsorb and desorb mercury in different ways and amounts. The purpose of writing this article is to review the results of previous research on the adsorption-desorption of mercury in soil so as to determine the extent of the risk of soil and environmental pollution. The method used in this writing is to collect and process data sources from previous research published in scientific articles, books, and discussion results. The results show that soils with high organic matter, iron oxide and clay content can absorb more Hg2+. In addition, lower pH has more hydroxylated surfaces that can adsorb more Hg2+. Irreversibility was found where the amount released or desorbed was less than the adsorption of mercury.